Lysosomal TMEM165 remodels calcium signaling to drive hypoxia adaptation and tumor progression - Yu Zeng; Meiting Chen; Yu Cao; Yan Huang; Xingguo Yang; Qian Jiang; Jiamin Huang; Yu Chen; Xin Du; Wenping Zeng; Qiankun Mao; Huafeng Zhang; et al. (Proceedings of the National Academy of Sciences, 2026)
Hypoxia is a common stress encountered by animal tissues during development, physiology, and disease. To cope with hypoxic stress, cells remodel metabolic and signaling networks to preserve viability and function. Lysosomes serve as central hubs for metabolic control and intracellular signaling, yet their role in hypoxic adaptation remains unclear. Here, we identify the lysosomal calcium transporter TMEM165 as a hypoxia-responsive regulator of cellular homeostasis. Under hypoxic conditions, TMEM165 expression increases, promoting calcium redistribution from the endoplasmic reticulum to lysosomes and expanding lysosomal calcium storage capacity. TMEM165 activation regulates autophagy and senescence through the AMPK-mTOR and ERK/p21 signaling pathways, respectively. In glioma, high TMEM165 expression correlates with poor prognosis, whereas its depletion suppresses glycolysis, proliferation, and tumor progression. These findings establish TMEM165 as a lysosomal hypoxia-responsive protein that integrates calcium signaling with metabolic and stress-response pathways, revealing a mechanistic link between oxygen availability, lysosomal function, and tumor adaptation.